Counselling in a Manitoba Community College - Curtis, David W. (Canadian Journal of Counselling and Psychotherapy, 2012)
This article presents a personal view of counselling- in Manitoba's largest community college. From an experiential background as teacher and counsellor of both adolescents and adults, the author examines the "training" philosophy of the community college, the historical antecedents of this philosophy, and the implications for the community college student and student personnel worker. The role of the college counsellor as a guidance worker or counsellor is also discussed. Related to this question is the apparent lowering of educational and professional qualifications for college counselling as a consequence of a guidance oriented system.A suggestion is made for the need of a national association of community college counsellors and for a publication to improve communication and awareness among student personnel workers related to the needs, practices, and concerns experienced in college counselling in Canada.